Underground Karst Stratification in Covered Karst Areas Under Control of River Valley Evolution: A Case Study of Baishiyao Hydropower Station - CHEN Qijun; LI Zhensong; LI Ningxin; ZHAN Jie (Renmin Zhujiang)
The underground karsts of the river valley in the covered karst area generally have the characteristics of vertical zoning with a strong upper part and a weak lower part.The causes of such vertical zoning are still unclear,which brings difficulties to practical engineering applications.Therefore,the multi-phase superimposed stratification model of river valley karsts is simplified to the three-phase superimposed strengthening model of underground karsts of the river valley.The simplification is conducted on the basis of finding out the characteristic karstification heads such as the maximum karstification head,the maximum strengthening head,and the latest strengthening head in the evolution process of the river valley from the canyon period to the basin period.The three-phase superimposed strengthening model is divided into the deep isolated cave layer,middle enhanced karst layer,and modern karst-influenced layer from bottom to top.Taking the Baishiyao Hydropower Station as an engineering example,this study analyzes the evolution of the river valley and the stratification of the underground karst profile.It is proposed that as the modern karst-influenced layer of the dam foundation is strongly developed,it is the key point of anti-seepage.The maximum anti-seepage depth of karsts should enter the middle enhanced karst layer to greatly lessen the anti-seepage treatment of karst leakage of the dam foundation and save engineering investment.Years of leakage observation suggest that the anti-seepage effect is good.The underground karst stratification in the covered karst area is of certain practical significance and can be used as a reference for the seepage prevention engineering of similar dam foundations.